Depressive symptoms in asymptomatic stage B heart failure with Type II diabetic mellitus - Mills, Paul J. (Clin Cardiol, 2019)
BACKGROUND: The presence of concomitant Type II diabetic mellitus (T2DM) and depressive symptoms adversely affects individuals with symptomatic heart failure (HF). HYPOTHESIS: In presymptomatic stage B HF, this study hypothesized the presence of greater inflammation and depressive symptoms in T2DM as compared to non‐T2DM Stage B patients. METHODS: This cross‐sectional study examined clinical parameters, inflammatory biomarkers, and depressive symptoms in 349 T2DM and non‐T2DM men with asymptomatic stage B HF (mean age 66.4 years ±10.1; range 30‐91). RESULTS: Fewer diabetic HF patients had left ventricular (LV) systolic dysfunction (P < .05) although more had LV diastolic dysfunction (P < .001). A higher percentage of T2DM HF patients were taking ACE‐inhibitors, beta‐blockers, calcium channel blockers, statins, and diuretics (P values < .05). T2DM HF patients had higher circulating levels of interleukin‐6 (IL‐6) (P < .01), tumor necrosis factor‐alpha (P < .01), and soluble ST2 (sST2) (P < .01) and reported more somatic/affective depressive symptoms (Beck Depression Inventory II) (P < .05) but not cognitive/affective depressive symptoms (P = .20). Among all patients, in a multiple regression analysis predicting presence of somatic/affective depressive symptoms, sST2 (P = .026), IL‐6 (P = .010), B‐type natriuretic peptide (P = .016), and sleep (Pittsburgh Sleep Quality Index [P < .001]) were significant predictors (overall model F = 15.39, P < .001, adjusted R (2) = .207). CONCLUSIONS: Somatic/affective but not cognitive/affective depressive symptoms are elevated in asymptomatic HF patients with T2DM patients. Linkages with elevated inflammatory and cardiac relevant biomarkers suggest shared pathophysiological mechanisms among T2DM HF patients with somatic depression, and these conditions are responsive to routine interventions, including behavioral. Copyright © 2019 John Wiley & Sons, Ltd.